A river called time, a house called land: Ethics and aesthetics (Ágora Journal, 2023)
This paper analysis of the book Um rio chama tempo, uma casa chama terra, by Mia Couto, having as a problem the appreciation in two dimensions: the ethical face of death and the relationship between man and nature, through bibliographical analysis , using hermeneutics. The exercise of mimesis is not related to the false, although it is not directly related to reality. Precisely for this reason, seeking the resolution of both problems ends up placing the person before the historical-philosophical task, since the work of art, as stated by Luiz Costa Lima, in order to dialogue with the interlocutor, keeps within itself the verisimilitude. The novelistic language is the creator of a fictional world that, although it does not exist on the physical plane, contributes to inquiring in search of an ethics that helps us to understand the world that surrounds us.
Keywords: Mimesis; ethic; art; fiction; history